The appropriate educational orientation (Docentes 2.0 Journal, 2016)
The search for strategies is not simply about incorporating technology in the educational field. A correct orientation of the roles played by each of the elements involved in the educational process is required. Recognizing the importance of appropriate educational guidance, it is considered necessary to briefly review the basic pedagogical aspects. This allows us to indicate more precisely what are the adjustments that have been made to deal positively with the prevailing technological reality.
Keywords: appropriate educational; orientation